2019
DOI: 10.3390/cells8111460
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Enhances Adipogenesis by Inhibiting Wnt/β-Catenin Expression

Abstract: Carbamazepine is a drug that is widely used in the treatment of epilepsy and bipolar disorder. The prevalence of obesity in patients treated with carbamazepine has been frequently reported. However, whether carbamazepine affects adipogenesis, one of the critical steps in the development of obesity, remains unclear. Here, we show that carbamazepine increased the expression levels of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein β (C/EBPβ), and fatty acid synthase (FASN) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…44 The antiepileptic drug carbamazepine (an inhibitor of voltage-gated sodium channels 45 ) has been shown to decrease Wnt/β-catenin signaling in the human colon adenocarcinoma SW480 cell line 34 and mouse adipocyte 3T3-L1 cells. 33 The results presented here contribute further evidence that Wnt signaling modulation may be involved in carbamazepine treatment of epilepsy. This warrants further studies of the role of Wnt-FZD8 signaling modulation in the therapeutic mechanism of carbamazepine against epilepsy.…”
Section: ■ Discussion and Conclusionsupporting
confidence: 64%
“…44 The antiepileptic drug carbamazepine (an inhibitor of voltage-gated sodium channels 45 ) has been shown to decrease Wnt/β-catenin signaling in the human colon adenocarcinoma SW480 cell line 34 and mouse adipocyte 3T3-L1 cells. 33 The results presented here contribute further evidence that Wnt signaling modulation may be involved in carbamazepine treatment of epilepsy. This warrants further studies of the role of Wnt-FZD8 signaling modulation in the therapeutic mechanism of carbamazepine against epilepsy.…”
Section: ■ Discussion and Conclusionsupporting
confidence: 64%
“…A recent study showed that raloxifene could reduce fat accumulation and suppress the activation of adipogenic factors by preserving the expression of canonical Wnt10b/β-catenin 45 . Moreover, carbamazepine inhibits Wnt/β-catenin expression and enhances adipogenesis 46 . In addition to the function of β-catenin in adipogenesis, a disruption of OCT4 and β-catenin recruitment to target gene promoters may affect differentiation, pluripotency, and cell cycle genes 47 .…”
Section: Discussionmentioning
confidence: 99%
“…De novo mutation of FASN in synaptic transmission genes was detected in epileptic encephalopathies via synaptic dysregulation ( 37 ). Carbamazepine increased the expression levels of FASN, suppressed Wnt/β-catenin expression, and was widely used in the treatment of epilepsy ( 38 ). 17-beta-hydroxysteroid dehydrogenase (HSD17B) plays a crucial role in catalyzing the androgen and estrogen biosynthesis in epileptic human hippocampus ( 39 ).…”
Section: Discussionmentioning
confidence: 99%